2021
DOI: 10.3390/ani11082428
|View full text |Cite
|
Sign up to set email alerts
|

Replacing Soybean Meal with Distillers Dried Grains with Solubles plus Rumen-Protected Lysine and Methionine: Effects on Growth Performance, Nutrients Digestion, Rumen Fermentation, and Serum Parameters in Hu Sheep

Abstract: (1) Background: we investigated the influence of dietary soybean meal (SBM) replaced with distillers dried grains with solubles (DDGS) plus rumen-protected (RP) lysine and methionine on the growth performance, nutrients digestion, rumen fermentation, and serum parameters of Hu sheep. (2) Methods: ninety Hu sheep were allocated to five groups: the control group (CON) which received the SBM diet, the DDGS group (NSM), the DDGS diet with RP lysine group (DRPL), the DDGS diet with RP methionine group (DRPM), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
3
6
0
Order By: Relevance
“…Fat tail decrease (p<0.05) to 2.04 kg in protected methionine treatment than control 3.39 kg, conversely kidney fat was higher in protected methionine treatment 0.079 kg than control treatment 0.066 kg while mesenteric fat was nearest in the two treatments 0.409 and 0.431 kg respectively, likewise no significant differences were noted in the non-carcass component. Our result was agreement with data of Obiedat et al (2008); Wang et al (2018) and Chen et al (2021) they report that feeding with protected methionine did not affect in carcass characteristics with a decrease in fat tail in lambs, in contrast with Li et al (2020) indicated that feeding with rumen protected methionine led to significant increase in carcass fat.…”
Section: Carcass Traitssupporting
confidence: 93%
“…Fat tail decrease (p<0.05) to 2.04 kg in protected methionine treatment than control 3.39 kg, conversely kidney fat was higher in protected methionine treatment 0.079 kg than control treatment 0.066 kg while mesenteric fat was nearest in the two treatments 0.409 and 0.431 kg respectively, likewise no significant differences were noted in the non-carcass component. Our result was agreement with data of Obiedat et al (2008); Wang et al (2018) and Chen et al (2021) they report that feeding with protected methionine did not affect in carcass characteristics with a decrease in fat tail in lambs, in contrast with Li et al (2020) indicated that feeding with rumen protected methionine led to significant increase in carcass fat.…”
Section: Carcass Traitssupporting
confidence: 93%
“…Among treatment comparisons, the molar ratios of acetate and the acetate: propionate ratio decreased as DDGS inclusion increased. Although conflicting results have been reported in the literature, the outcomes of our meta-analysis suggest that the excess bypass protein in DDGS was connected to decreased rumen fermentation (3,31). Also, the dose-response analysis supports the hypothesis that dietary DDGS in meat sheep should not exceed 20% to prevent negative effects on rumen fermentation.…”
Section: Discussionsupporting
confidence: 72%
“…2 No DDGS in the diet. 3 Raw mean difference between control vs DDGS treatment. 4 p-value for X 2 (Q) test for heterogeneity; I 2 , Proportion of total variation of size effect estimated due to heterogeneity.…”
Section: Carcass Characteristicsmentioning
confidence: 99%
“…Distillers' grain (DG), a cereal byproduct of ethanol production, has high nutritional value because of the removal of starch during the fermentation process and the consequent increase in digestible fiber, protein, and fat; China generates ~100 million tons of DG each year ( 2 , 3 ). DG is used as a source of protein and energy due to its high protein and fat contents ( 4 ). Reis et al ( 5 ) found that feeding dried DG improved the growth performance and meat quality of bulls.…”
Section: Introductionmentioning
confidence: 99%